PENINGKATAN HASIL BELAJAR IPAS PADA MATERI SIKLUS HIDUP HEWAN MELALUI MODEL PROBLEM BASED LEARNING PADA SISWA KELAS III SDN DANAU INA OESAPA KOTA KUPANG - Theodora Luruk; Antonius Suban Hali; Netty E.A. Nawa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Luruk, Theodora 1901140095 PGSD. “Improving the ability to learn science on the subject of animal life cycles through the problem based learning model in class IIIA students of SDN Danau Ina Oesapa Kupang”. Antonius suban Hali, S,Si. M,Si as the first supervisor, Netty E.A Nawa, S,Pd. M,Pd as the second supervisor.This study aims to improve the learning outcomes of sciences in the animal life cycle material through the problem based learning (PBL) learning model in class IIIA students of SDN Danau Ina Oesapa. This type of research is Classroom Action Research (CAR). Data collection is used using teacher activity observation sheets, students activity observations and student learning outcomes tets. This data is analyzed using qualitative study. show that in cyle I, there were 10 students who completed the material with a percentage of (43,84%) while 13 others did not complete it with a percentage of ( 56,52%). Then in cycle II, as many as 21 students completed it with a percentage of 91,3% while 2 students did not complete it with a percentage of (8,7%). Thus, it can be concluded that the application of the established problem based learning (PBL) learning model can improve student learning outcomes at SDN Danau Ina Oesapa Kupang.